Systematic review of genome-wide association studies of abdominal aortic aneurysm. (June 2021) - Singh, Tejas P.; Field, Matt A.; Bown, Matthew J.; Jones, Gregory T.; Golledge, Jonathan
Abstract: Background and aims: Abdominal aortic aneurysm (AAA) is an important cause of death worldwide and has an estimated heritability between 70 and 77%. Genome-wide association studies (GWAS) are an established way to discover genetic risk variants. The aim of this study was to systematically review the findings and quality of previous AAA GWAS. Methods: The Medline, PubMed, Web of Science and relevant genetic databases were searched to identify previous AAA GWAS. A framework was developed to grade the methodological quality of the GWAS. Data from included studies were extracted to assess methods and findings. Results: Eight case-control studies were included. Thirty-three of the 38 total single nucleotide polymorphisms (SNPs) previously reported were associated with AAA diagnosis at genome-wide significance ( p  < 5.0 × 10 −8 ). The CDKN2B antisense RNA-1 gene had the most significant association with AAA diagnosis ( p  = 6.94 × 10 −29 and p  = 1.54 × 10 −33 for rs4007642 and rs10757274 respectively). Age, sex and smoking history were not reported for the complete cohort in any of the included studies, although five of the eight studies adjusted or matched for at least two confounding variables. All included studies had important design limitations including lack of sample size estimation, inconsistent case and control ascertainment and limited phenotyping of the AAAs. AAA growth was assessed in one GWAS, however, no significant associations with the reported SNPs were found. Conclusions: This systematic review identified 33 SNPs associated with AAA diagnosis at genome-wide significance previously validated in multiple cohorts. The association between SNPs and AAA growth was not adequately examined. Previous GWAS have a number of design limitations. Graphical abstract: Image 1 Highlights: Previous case-control studies have estimated the heritability of abdominal aortic aneurysm (AAA) to be between 70 and 77%. Prior genome wide association studies have identified single nucleotide polymorphisms (SNPs) associated with AAA diagnosis. This systematic review identified 33 SNPs associated with AAA diagnosis at genome-wide significance.